Candhik Ayu: canon of life philosophy for Mangkunegaran Princesses - Dhian Lestari Hastuti; Imam Santosa; Achmad Syarief; Pribadi Widodo (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2022)
Place identity is related to the identity of its residents. This study reveals the concept of Pracimoyoso Hall at Dalem Keputren Pracimosono to find the colour concept that represents the canon of life philosophy for the Mangkunegaran princesses. This research applies the qualitative method, descriptive analysis, and a semiology approach by considering architecture as a sign system. The data were collected from document analysis, in-depth interviews, and field observations. Babad Tutur, Serat Jatimurti, and Serat Wedhatama were analyzed to find out the formation of women's characters as well as their roles and positions within Mangkunegaran Palace. The semiology approach is used to decode the meanings of the three books. Then the meanings are used to analyze the characters of the princesses through the semiological analysis of the physical forms of Pracimoyoso Hall to obtain the concepts. The results show that semiology can reveal the pink to the purple spectrum of candhik ayu as the canon of life philosophy for the Mangkunegaran princesses. This research contributes to providing new insights into the concept of colours as the canon of life philosophy by understanding the relationship between a place's identity and its residents' self-identity through the identification of the serat books and their implementation in architecture as a sign system